Neanderthals in the desert? Population history best explains Middle Palaeolithic technological heterogeneity in Arabia - James Blinkhorn; Huw S. Groucutt; W. Christopher Carleton; Eric Andrieux; Simon J. Armitage; Ceri Shipton; Paul S. Breeze; Nick Drake; Abdulaziz Al-Omari; Faisal Al-Jibreen; Abdullah M. Alsharekh; Eleanor M.L. Scerri; et al. (Quaternary Science Reviews, 2026)

Adaptive area-wide management for suppressing spruce budworm outbreaks: effectiveness of the early intervention strategy - Rob C. Johns; S. Edwards; L. Amos-Binks; J. J. Bowden; D. Carleton; C. Edge; C. Hennigar; P. James; D. MacLean; V. Martel; E. R. D. Moise; B. Morin; et al. (Journal of Pest Science, 2026)
In eastern North America, two main insecticide-based strategies are used to manage spruce budworm ( Choristoneura fumiferana ) outbreaks. The traditional ‘Foliage Protection Strategy’ (FPS) focuses on temporarily reducing defoliation and tree mortality in high-value stands, allowing outbreaks to progress naturally in surrounding areas. The ‘Early Intervention Strategy’ (EIS) is an adaptive, area-wide management approach that targets low-density “hotspots” to prevent outbreak growth and spread. We report findings from a 10-year case study (2015–2024) in Atlantic Canada assessing EIS effectiveness. EIS treatments consistently reduced population growth rates, resulting in a 12–67% reduction in hotspot areas compared to untreated areas. Crucially, this suppression curbed the rise and spread of the outbreak across northern New Brunswick, with negligible defoliation observed throughout the study period. By comparison, in a neighboring Quebec study area contemporaneously managed with FPS, the outbreak advanced normally, causing moderate to severe defoliation over ~ 1.7 million hectares by 2024. Moreover, EIS required ~ 80% less insecticide, with 66% of treated areas receiving treatment in only a single year, compared with just 15% under FPS. Our findings provide robust evidence for the effectiveness of EIS when implemented under suitable conditions, highlighting its potential as a proactive outbreak management approach.

Nutrient explorer: An analytical framework to visualize and investigate drivers of surface water quality - Michael J. Pennino; Meridith M. Fry; Robert D. Sabo; James N. Carleton (Environmental Modelling & Software, 2023)

Historical pesticide applications for the treatment of eastern spruce budworm infestations in New Brunswick - Shane Heartz; David A. MacLean; Rob C. Johns; Drew Carleton; Luke Amos‐Binks; Quinn Anderson; Yue Yu; Andrew D. Lewis; Dan Lavigne; Joseph B. Burant; Christopher B. Edge (Ecology, 2023)
Pesticides have been used in Canada since 1945 as part of large‐scale aerial spray applications to control insect pests on forested lands. Some of the pesticides used historically were efficacious, nonselective, persistent, and have led to serious impacts on the environment. A well known, and extensively documented example is the large‐scale aerial spray programs in New Brunswick, Canada. From 1952 to 1993, 97% of the 6.2 million ha of the forested lands of New Brunswick were treated with at least one application of one insecticide, the majority of which were applied to control outbreaks of eastern spruce budworm ( Choristoneura fumiferana ). The most well known insecticide was dichlorodiphenyltrichloroethane (DDT), applied from 1952 to 1968, which still persists in treated soils and adjacent water bodies, and caused the individual and cumulative ecosystem effects that can still be measured today. The insecticides that replaced DDT were nonpersistent and unlikely to be found today. However, during the years of application some of the insecticides were likely to have impacted local ecosystems to some degree. To aid future studies on the efficacy and environmental impact of these insecticides we created a digital spatial data set of known pesticide application in New Brunswick forestry from 1952 to 1993. The data set includes active ingredient, formulation, application rate, tank mix, aircraft type, and other ancillary information. The current version of the data is available on the New Brunswick Department of Natural Resources and Energy Development, GIS Open Data Page and in the supplemental material. Use of the data set for academic and educational purposes is encouraged, provided that both this data paper and the data source are properly cited; the Government of New Brunswick should be acknowledged as the data source (Open Government License http://www.snb.ca/e/2000/data-E.html ).

Association between recent U.S. northeast precipitation trends and Greenland blocking - Julia M. Simonson; Sean D. Birkel; Kirk A. Maasch; Paul A. Mayewski; Bradfield Lyon; Andrew M. Carleton (International Journal of Climatology, 2022)
Since the early 2000s, the northeastern region of the United States (USNE) has received increased total annual precipitation along with more frequent extreme precipitation events. Although previous work has discussed the contribution to increased extreme precipitation from tropical cyclones, the large‐scale driver(s) of summer precipitation increases in the extratropics has received little attention. Here, we show that the summer‐season rainfall surpluses across the USNE are related to the increased frequency of atmospheric blocking over Greenland and the negative phase of the North Atlantic Oscillation. The occurrence of these patterns in summer has been previously connected with southward shifted storm tracks and wet conditions across the eastern North Atlantic. Over the USNE, the circulation shifts are also related to enhanced rainfall due to southerly wind anomalies and increased moisture transport into and vertical motion over the region. It is important to note that the current generation of climate models used for future projections is unable to reproduce the observed tendency towards increased atmospheric blocking over Greenland. Thus, clarifying the association between Greenland blocking and recent precipitation changes across the USNE may help inform future climate projections of summer season rainfall for the region.

Movement of transposable elements contributes to cichlid diversity - Karen L. Carleton; Matthew A. Conte; Milan Malinsky; Sri Pratima Nandamuri; Benjamin A. Sandkam; Joana I. Meier; Salome Mwaiko; Ole Seehausen; Thomas D. Kocher (Molecular Ecology, 2020)
African cichlid fishes are a prime model for studying speciation mechanisms. Despite the development of extensive genomic resources, it has been difficult to determine which sources of genetic variation are responsible for cichlid phenotypic variation. One of their most variable phenotypes is visual sensitivity, with some of the largest spectral shifts among vertebrates. These shifts arise primarily from differential expression of seven cone opsin genes. By mapping expression quantitative trait loci (eQTL) in intergeneric crosses of Lake Malawi cichlids, we previously identified four causative genetic variants that correspond to indels in the promoters of either key transcription factors or an opsin gene. In this comprehensive study, we show that these indels are the result of the movement of transposable elements (TEs) that correlate with opsin expression variation across the Malawi flock. In tracking the evolutionary history of these particular indels, we found they are endemic to Lake Malawi, suggesting that these TEs are recently active and are segregating within the Malawi cichlid lineage. However, an independent indel has arisen at a similar genomic location in one locus outside of the Malawi flock. The convergence in TE movement suggests these loci are primed for TE insertion and subsequent deletions. Increased TE mobility may be associated with interspecific hybridization, which disrupts mechanisms of TE suppression. This might provide a link between cichlid hybridization and accelerated regulatory variation. Overall, our study suggests that TEs may be an important driver of key regulatory changes, facilitating rapid phenotypic change and possibly speciation in African cichlids.

Visual adaptation could aid sympatric speciation in a deep crater lake - Karen L. Carleton; Daniel Escobar‐Camacho; Thomas D. Kocher (Molecular Ecology, 2019)
Allopatric speciation was originally suggested to be the primary mechanism of animal speciation (Mayr, 1942; Figure 1). During allopatric speciation, populations diverge when gene flow is reduced across significant biogeographic barriers. Sympatric speciation, where species diverge while inhabiting the same location, was thought to be essentially impossible. However, the advent of theoretical models followed by new experimental evidence made sympatric speciation more plausible (Via, 2001). The cichlid fishes of Barombi Mbo, a small crater lake in western Cameroon, became one of the most widely accepted examples of sympatric speciation (Schliewen, Tautz, & Paabo, 1994). Although the phylogenetic history of this clade is not quite as simple as originally thought, it remains one of the best examples of sympatric speciation (Richards, Poelstra, & Martin, 2018). However, little is known about the molecular mechanisms contributing to the splitting of these species in situ. In a From the Cover article in this issue of Molecular Ecology , Musilova et al. (2019) focus on the diversity of visual systems among these fishes. They identify genetic changes associated with several aspects of visual adaptation that may have contributed to the ecological specialization and sympatric speciation of cichlids in this lake.

Potential for Southern Hemisphere climate surprises - P. A. MAYEWSKI; T. BRACEGIRDLE; I. GOODWIN; D. SCHNEIDER; N. A. N. BERTLER; S. BIRKEL; A. CARLETON; M. H. ENGLAND; J‐H. KANG; A. KHAN; J. RUSSELL; J. TURNER; et al. (Journal of Quaternary Science, 2015)
Climate model results suggest that future climate change in Antarctica will be accompanied by continued strengthening and poleward contraction of the Southern Ocean westerly wind belt. Paleoclimate records suggest past changes in the westerly winds can be abrupt and that healing of the Antarctic ozone hole could lead to poleward contraction of the westerlies and increased meridional atmospheric transport of warm air regionally into Antarctica. An abrupt shift to more meridional circulation could lead to notable changes in moisture availability for extra‐Antarctic regions, increased Antarctic ice sheet disintegration and more rapid sea‐level rise.

Land cover changes and their biogeophysical effects on climate - Rezaul Mahmood; Roger A. Pielke; Kenneth G. Hubbard; Dev Niyogi; Paul A. Dirmeyer; Clive McAlpine; Andrew M. Carleton; Robert Hale; Samuel Gameda; Adriana Beltrán‐Przekurat; Bruce Baker; Richard McNider; et al. (International Journal of Climatology, 2014)
Land cover changes ( LCCs ) play an important role in the climate system. Research over recent decades highlights the impacts of these changes on atmospheric temperature, humidity, cloud cover, circulation, and precipitation. These impacts range from the local‐ and regional‐scale to sub‐continental and global‐scale. It has been found that the impacts of regional‐scale LCC in one area may also be manifested in other parts of the world as a climatic teleconnection. In light of these findings, this article provides an overview and synthesis of some of the most notable types of LCC and their impacts on climate. These LCC types include agriculture, deforestation and afforestation, desertification, and urbanization. In addition, this article provides a discussion on challenges to, and future research directions in, assessing the climatic impacts of LCC .

Gender-Dependence of Bone Structure and Properties in Adult Osteogenesis Imperfecta Murine Model - Xiaomei Yao; Stephanie M. Carleton; Arin D. Kettle; Jennifer Melander; Charlotte L. Phillips; Yong Wang (Annals of Biomedical Engineering, 2013)

Cancer Prevention Interdisciplinary Education Program at Purdue University: Overview and Preliminary Results - Dorothy Teegarden; Ji-Yeon Lee; Omolola Adedokun; Amy Childress; Loran Carleton Parker; Wilella Burgess; Julie Nagel; Deborah W. Knapp; Sophie Lelievre; Christopher R. Agnew; Cleveland Shields; James Leary; et al. (Journal of Cancer Education, 2011)

Post-Fire Resource Redistribution in Desert Grasslands: A Possible Negative Feedback on Land Degradation - Sujith Ravi; Paolo D’Odorico; Lixin Wang; Carleton S. White; Gregory S. Okin; Stephen A. Macko; Scott L. Collins (Ecosystems, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Zooplankton In An Australian Tropical Estuary - S. Duggan; A. D. McKinnon; J. H. Carleton (Estuaries and Coasts, 2008)

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

Antarctic climate change during the last 50 years - John Turner; Steve R. Colwell; Gareth J. Marshall; Tom A. Lachlan-Cope; Andrew M. Carleton; Phil D. Jones; Victor Lagun; Phil A. Reid; Svetlana Iagovkina (International Journal of Climatology, 2005)

Estimating the patch size of larval fishes during colonization on coral reefs - D. Lecchini; V. Dufour; J. Carleton; S. Strand; R. Galzin (Journal of Fish Biology, 2004)
Fish larvae were sampled daily over a period of 14 days using six crest nets spaced at 200 m intervals on a coral reef on the west coast of Moorea Island, French Polynesia, to estimate the extent to which ichthyonekton arriving at one location reflected ichthyonekton arriving at neighbouring areas. Each night, the six crest nets were colonized by larval fishes from the same location.